Implementasi Nilai Tauhid Dalam Kegiatan Ekologi di Pondok Pesantren As-Salafiyyah Mlangi, Gamping, Sleman, Yogyakarta - Chaza Afida Amna; Muhammad Syauqi Firdaus; Elyza Riana; Sinta Maryana; Al-Fath Faizal Syahbana; Rizal Fathurrohman (PT. Nawa Edukasi Nusantara, 2025)
This study aims to describe the implementation of tawhid values in maintaining environmental cleanliness within Islamic boarding schools (pesantren). Tawhid, as the core principle of Islamic teaching that emphasizes the oneness of Allah, serves as a moral and spiritual foundation for daily behavior, including environmental care. This research employed a qualitative approach through observations and interviews with pesantren administrators and students. The findings indicate that awareness of tawhid motivates students to care for their environment as a form of responsibility toward Allah’s creation. Regular cleaning activities are conducted as part of religious practice, such as picking up litter, nurturing plants, and maintaining a clean and healthy environment. The pesantren also instills the value of cleanliness through routine practices and religious education that are directly connected to the doctrine of tawhid. This study concludes that tawhid values help shape students' environmental awareness, making cleanliness an integral part of their faith and the holistic implementation of Islamic teachings.